2021
DOI: 10.1159/000515035
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome Depletion-Triggered Autophagy Impairment in Progressive Kidney Injury

Abstract: <b><i>Background:</i></b> Macroautophagy (autophagy) is a cellular recycling process involving the destruction of damaged organelles and proteins in intracellular lysosomes for efficient nutrient reuse. <b><i>Summary:</i></b> Impairment of the autophagy-lysosome pathway is tightly associated with multiple kidney diseases, such as diabetic nephropathy, proteinuric kidney disease, acute kidney injury, crystalline nephropathy, and drug- and heavy metal-induced renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…60 Autophagic flux represents a major adaptive and restorative response; impairment of autophagy dramatically heightens the likelihood that an injurious event will lead to cardiomyopathy and nephropathy. 139,140 Although excessive stimulation of autophagy may exert deleterious effects on the heart (particularly after acutely imposed massive stresses in the absence of HF), 141,142 measured augmentation of selective autophagy protects the heart against pressure overload, hypoxia, and injury produced by cardiotoxic agents, 143,144 and shields podocytes and renal tubular cells from damage caused by diabetes, ischemia, and nephrotoxic drugs. 145,146 Autophagic vacuoles are increased in patients who show reverse cardiac remodeling or receive mechanical unloading, 147,148 whereas persistent impairment in autophagy flux in the failing human heart is a poor prognostic sign.…”
Section: Action Of Nutrient Sensors To Influence Cellular Stress By M...mentioning
confidence: 99%
“…60 Autophagic flux represents a major adaptive and restorative response; impairment of autophagy dramatically heightens the likelihood that an injurious event will lead to cardiomyopathy and nephropathy. 139,140 Although excessive stimulation of autophagy may exert deleterious effects on the heart (particularly after acutely imposed massive stresses in the absence of HF), 141,142 measured augmentation of selective autophagy protects the heart against pressure overload, hypoxia, and injury produced by cardiotoxic agents, 143,144 and shields podocytes and renal tubular cells from damage caused by diabetes, ischemia, and nephrotoxic drugs. 145,146 Autophagic vacuoles are increased in patients who show reverse cardiac remodeling or receive mechanical unloading, 147,148 whereas persistent impairment in autophagy flux in the failing human heart is a poor prognostic sign.…”
Section: Action Of Nutrient Sensors To Influence Cellular Stress By M...mentioning
confidence: 99%
“…Autophagy-dependent cell death is a natural degradation process of cellular contents and a rare kind of PCD [ 33 35 ]. During autophagy-dependent cell death, extensive vacuolization of the cytoplasm is formed; the integrity of the plasma membrane is lost; and sometimes, enlargement of the Golgi and ER is observed [ 36 38 ].…”
Section: Ferroptosis and Cell Deathmentioning
confidence: 99%
“…These differential proteins were regrouped by unsupervised hierarchical cluster analysis (Figure e), and the results showed that IgAN patients and healthy donors could be well separated, indicating the potential of using exosomal protein profiling for biomarker screening for IgAN patients. Moreover, pathway analysis of the differential proteins quantified in IgAN and healthy donors using DAVID with the KEGG database showed that “lysosome” ( P = 3.24 × 10 –6 ) and “extracellular membrane (ECM)–receptor interaction pathway” ( P = 2.55 × 10 –5 ) were two major pathways that were closely related to cell injury and the progression of renal fibrosis. , Finally, the biological implications of the significantly upregulated proteins were studied. Among them, as high as 38.3% of the 47 significantly upregulated proteins (Table S4) such as AFM, ORM1, CP, SERPINA1, and C3 were previously reported to be closely related to IgAN. Besides, among the proteins that were not previously found to have a direct association with IgAN, carbonic anhydrase 1 (CA1, 47.5 times, P = 6.51 × 10 –6 ), desmocollin-1 (DSC1, 5.51 times, P = 0.000683), tissue α- l -fucosidase (FUCA1, 3.15 times, P = 0.00297), and peroxiredoxin-2 (PRDX2, 2.85 times, P = 0.00484) were reported to play important roles in prevention of oxidative damage, regulation of basal immunity, and function of kidney injury. Further validation of the relationship between such proteins with IgAN is ongoing.…”
Section: Results and Discussionmentioning
confidence: 99%